(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The question of choice of law by the parties is one of the fundamental features of the principle. This feature is one of the main components of the principle. It primarily enables us to help understand the fundamental basis of the principle. This article discusses the issues of choice of law by agreement of the parties based on the principle of autonomy of will. One of the controversial issues is the possibility of the parties choosing the law based on their contract. The origin and development of this fundamental right requires a long period of time. In the article, the origin and development of this right will be analyzed by dividing into stages and the features of its development in each period are studied. Through long history of the principle’s development, scholars studied and observed the significance of parties’ intention and right to choose which law should govern their contractual relationships. In the article, the period of development of the principle is conventionally divided into two. The first period is the stage when this principle was secondary importance to legislators and contractors, and parties’ freedom to choose the governing law was limited. In the second stage, parties’ freedom of choice gained paramount importance from state legislators and the restrictions on parties were notably reduced. Each stage of this development increasingly served firmly established state rules to give leeway parties’ intentions to choose the governing for their contractual relationships.